Profile and Clinical Character of COVID-19 Patients at Zahirah Hospital, South Jakarta: Profil dan Karakter Klinis Pasien COVID-19 di Rumah Sakit Umum Zahirah, Jakarta Selatan - Nur Hasanah; Lela Kania Rahsa Puji; Nurwulan Adi Ismaya; Vini Irnia; Fenita Puranamasari Indah (Universitas Tadulako, 2022)
Background: The rapid spread of COVID-19 makes people anxious and afraid of this outbreak. The government has implemented policies to prevent the spread of the corona virus. One of the implementations is Large-Scale Social Restrictions. This condition causes a considerable impact on several sectors, especially health, economy and education. Objectivity: this study was to determine the characteristics of COVID-19 patients receiving treatment at Zahirah General Hospital. Material and methode: Methode of the research is observational with a cross sectional design with a total sample of 328. Result: The results showed that the most cases of COVID-19 occurred at the age Late seniors (43%), male sex as much as 52%, experiencing fever (97%), the most comorbid disease was diabetes as much as 56%, treatment carried out by giving antivirals+supplements (79%), all patients were given supplements in the form of: Acetylcysteine, Vitamin C, B-complex, Zinc, Vitamin D. Avigan/ favipiravir was the most widely used antiviral (42%), the length of time the patient was treated for 14-21 days (41%), All COVID-19 patients with comorbidities show lymphocyte levels that are lower than normal limits. Conclusion: Late seniors, men are more susceptible to COVID-19 infection, diabetes is the comorbid disease that causes death and the most severe COVID-19 symptoms, and all COVID-19 patients with comorbidities have lower lymphocyte levels